Factors stimulating value micro-businesses attribute to digital marketing technology (DMT) adoption - Eze, Sunday C.; Chinedu-Eze, Vera C.; Awa, Hart O.; Alharthi, Rami Hashem E. (PLOS ONE, 2021)
Most micro-business managers in Nigeria do not see the adoption of digital marketing technology (DMT) as vital for business. Many consider it as a precondition to support managerial or operational activities, not as a tactical and/or strategic tool. Although most studies focused on large organisations, the outcome of such research may not be appropriate to micro-businesses. This is informed by the negligence of micro-businesses’ idiosyncrasies and their thought of digitalization as a precondition for managerial activities without considering the value small businesses attached to these devices in terms of aiding the use as strategic tools. This renders micro-businesses’ digitalization an under-reflected phenomenon. Yet, studies spend less on examining the factors that specifically stimulate the value micro-businesses attach to these applications, leading to constant adoption and usage. Hence, there is a need for a thorough exploration of the factors that shape the value of digital marketing applications in micro-businesses in Nigeria. The study is qualitative in nature and interviews (unstructured and semi-structured) were carried out with 26 micro-businesses which was drawn purposefully from the online database and underpinned by Technology, Organisation and Environment (TOE) framework. The study revealed eleven (11) critical success factors stimulating value micro-businesses attribute to digital marketing technology (DMT) adoption. These factors include long-term functional capacity, integration capacity, expansion capacity which are related to technology context. Collective capability, collaborative experience are linked to the organisation context while adaptive training, service delivery, customer fulfilment are linked to environmental context. The study also unveiled expectancy context which is linked to budget, growth and profitability and aid in the extension of the TOE framework. This study will be of importance to academics and practitioners because it provides further awareness into DMT adoption framework, factors critical to the DMT adoption and may assist in reducing the number of resources spent in search of information aimed at helping DMT adoption by micro-businesses.